Inflammatory polyradiculoneuropathies: Clinical and immunological aspects, current therapies, and future perspectives. (November 2020) - Di Stefano, Vincenzo; Barbone, Filomena; Ferrante, Camilla; Telese, Roberta; Vitale, Michela; Onofrj, Marco; Di Muzio, Antonio
Inflammatory polyradiculoneuropathies are heterogeneous disorders characterized by immune-mediated leukocyte infiltration of peripheral nerves and nerve roots leading to demyelination or axonal degeneration or both. Inflammatory polyradiculoneuropathies can be divided into acute and chronic: Guillain–Barré syndrome and chronic inflammatory demyelinating polyneuropathy and their variants. Despite major advances in immunology and molecular biology have been made in the last years, the pathogenesis of these disorders is not completely understood. This review summarizes the current literature of the clinical features and pathogenic mechanisms of inflammatory polyradiculoneuropathies and focuses on current therapies and new potential treatment for the future.